The functional extracellular vesicles target tumor microenvironment for gastrointestinal malignancies therapy - Dongqi Li; Xiangyu Chu; Yudong Ning; Yinmo Yang; Chen Wang; Xiaodong Tian; Yanlian Yang (Extracellular Vesicle)
The tumor microenvironment (TME) represents a complex, heterogeneous ecosystem that significantly influences the progression of gastrointestinal (GI) cancers, comprising diverse cellular and non-cellular components. Although chemotherapeutic agents and targeted therapies offer partial benefits for patients with GI tumors, their efficacy remains limited due to the TME's complexity. Consequently, strategies to target and modulate the TME are critical to enhancing therapeutic outcomes. Extracellular vesicles (EVs) transport a wide array of biomolecules, including proteins, lipids, and nucleic acids, playing a pivotal role in intercellular communication and TME modulation. In recent years, EVs have gained attention as potential drug delivery vehicles, owing to their nanoscale size and capacity to shuttle bioactive molecules between cells and tissues. Moreover, engineered EVs hold promise for modulating the TME to treat GI cancers by improving targeting precision and tissue penetration. This review explores the latest strategies for the production and functionalization of EVs, along with advances in utilizing EVs for targeted therapy of the TME in GI tumor treatment.